Re-Connecting: a redevelopment of the Wynberg Precinct - Chokupermall, Jason Allan (School of Architecture, Planning and Geomatics, 2017)
This dissertation aims at motivating a redevelopment of the Wynberg Precinct which includes reconnecting the western and eastern fabric of the precinct which has been initially divided due to the installation of a train station. Wynberg is located in the southern suburb of Cape Town and is a highly active transport interchange which includes a train station and 3 taxis ranks with an estimated average daily density of 21,000 commuters. Subsequently, the high density of commuters transiting daily through the Wynberg precinct has consequently generated the opportunities for informal traders - street traders - to appropriate open spaces and street edges within the precinct to develop their micro enterprises. Associated together, the transport interchange, the street traders and commuters, had overtime shaped the character of the precinct and stimulate the public realm. This dissertation is also motivated by the current 'informal trading and mass commuting' phenomenon arising within the Wynberg precinct. The precinct is an arena for contest for spaces and spatial inclusivity between the street traders, commuters and taxis. The planning and configuration of the Wynberg precinct has predominantly been driven towards the integration of the train station and the taxis ranks but not much considerations have been placed on the integration of the street traders in the precinct. Consequently, as a result of such planning attitude, traders contest for space to trade, pedestrians contest for clear sidewalks while Taxis contest for clear streets without any obstructions. Furthermore, the dissertation also aims at reconnecting the commuter's routes between the transport facilities. There is a discontinuity in the commuter's routes from one transport facility to the other. Commuters are required to find alternative routes - using the street itself - to have access to their respective transport facilities since the street traders in the precinct occupies the sidewalks. Subsequently, using the street as a pedestrian route holds a further impact on the vehicular flow around the precinct.